Studies of the excretion of aluminium by the kidney and the toxic effects of the element on DNA - Monteagudo, Felix Salvador Emilio (Division of Clinical Pharmacology, 2018)
Aluminium is an element of increasing clinical importance. It not only has uses as a medicinal substance but also in recent years it has been shown to be the cause of considerable toxicity, particularly in the setting of chronic renal failure. Diseases that have been shown to be associated with aluminium, or in which it has been implicated, include dialysis dementia, renal osteodystrophy and Alzheimer's disease. This thesis has studied aspects of the interaction between aluminium and the kidney. The work has addressed two major issues. Firstly, a study is described where Malvin's stop-flow technique was used to determine any excretory/absorptive tubular site for Al in the pig kidney. Al was found to be excreted in the distal nephron of the pig kidney. Secondly, the toxic effects of Al in vitro on the DNA of pig kidney cell line LLC-PKl were investigated, in an attempt to elucidate some of the mechanisms of toxic action. DNA synthesis was measured using ³H-TdR incorporation. Over increases of both time (9-72 h) and Al concentration (0.01-8.0 mM), ³H-TdR incorporation was diminished. Effects were evident at concentrations as low as 0.05 mM Al. The production of DNA strand breaks was assessed by the increase in size of cell nucleoids (ie DNA in supercoiled form). Nucleoid size was analyzed in a Epics 753 Fluorescence Activated Cell Sorter interfaced with an MDADSII data acquisition and analysis system. After 90 min incubation with Al (over the concentration range 0.001-32 mM), an increase in nucleoid size was noted at concentrations above 0.05 mM. The data demonstrate that Al exerts an effect on kidney cells in vitro which is expressed as diminished DNA synthesis and production of DNA strand breaks. These effects on DNA may have important long-term implications on various disease states associated with Al toxicity.